Accountability and Transparency of Village Governance in the Management of the Village Revenue and Expenditure Budget - Wulandari Wulandari; Muhammad Fahmi; Syarif M Helmi; Nina Febriana Dosinta (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to examine the accountability and transparency of the Village Government in managing the Village Budget (APBDes) in Jongkong Kanan Village, Jongkong Sub-district, Kapuas Hulu Regency. This research employs a descriptive qualitative method with a case study approach. Data collection methods used in this study include interviews, observations, and documentation, categorized into two sources: primary and secondary data. The results of this study indicate that the accountability and transparency of the Jongkong Kanan Village Government in managing the APBDes have been implemented in accordance with the Ministry of Home Affairs Regulation (PERMENDAGRI) No. 20 of 2018. From the planning, implementation, administration, reporting, to accountability stages, all have been carried out properly. The application of the accountability principle is demonstrated through community involvement in deliberations related to the management of the APBDes. Meanwhile, the transparency principle is applied by providing information through the village website regarding infrastructure improvement and development processes, as well as through the installation of APBDes billboards in front of the village office. However, there are still several obstacles faced by the Jongkong Kanan Village Government, such as the lack of public interest in participating in village deliberations and challenges in the accountability reporting process, including delays in the return of financial accountability reports (SPJ) and frequently changing regulations.